How to Structure and Intensify Mathematics Intervention. (April 2022) - Powell, Sarah R.; Benz, Sarah A.; Mason, Erica N.; Lembke, Erica S.
Many students who experience difficulty with mathematics may also require behavioral support. We suggest educators create an appropriate scope and sequence for mathematics intervention by focusing on the critical mathematics content. Educators can then design the intervention with a common session structure. Finally, educators can embed and intensify supports for a student by increasing the dosage, focusing on the alignment of the intervention, and attending to transfer.